المسائل الفقهية النسائية المطبَّقة في المجتمع الجاوي ووجهة نظر الشرع فيها - Sahid, Mualimin Mohd; Mohamed, Mohd Faisal bin; Hoque, Mesbahul (Universitas Islam Indonesia, 2017)
THE SHARI'A'S PERSPECTIVE ON ISSUES RELATED TO WOMEN'S JURISPRUDENCE IN THE JAVANESE COMMUNITYAbstractJavanese Muslims have encountered variety of customs and local traditions practiced in their religious and social life, which are heavily influenced by ancient beliefs and religions. This influence has led to unique religious phenomenon, which mixes Islam with other beliefs. One of the most highlighted issues is traditions related to women's jurisprudence (fiqh al-nisâ`). This research aims to study some of the most important issues of women's jurisprudence applied in Javanese community and indicate wether they are appropiate from Islamic point of view, or not. This research has found that there are various javanese customs and traditions related to fiqh al-nisâ`, namely, traditions and beliefs about placenta, weight of child’s name, woman's engagement, circumcision of women, and unregistered marriage (al-nikâh al-sirri). Some of these traditional practices are influenced by old-traditional Javanese beliefs. Unfortunately, even these tradition try to maintain Islamic values in their local shape of practice, some of them are still in contrary to what Islam has stated. Therefore, this article states clearly that the right thing to deal with those customs is to abandon them that are contrary to Islamic law and to be satisfied with the practices allowed by the Islamic law. Keywords: Local Customs, Tradition, Javanese Muslim, Traditional Islam, Women's Issues, Sharia, Fiqh al-nisâ`.